Micropattern of core-shell Ag@MCS/PEGDA nanoparticles fabricated by femtosecond laser maskless optical projection lithography - Fan-Chun Bin; Xin-Yi Wu; Jie Liu; Xian-Zi Dong; Teng Li; Qi Duan; Jian-Miao Zhang; Katsumasa Fujita; Mei-Ling Zheng (International Journal of Extreme Manufacturing)
Chitosan (CS)-based nanocomposites have been studied in various fields, requiring a more facile and efficient technique to fabricate nanoparticles with customized structures. In this study, Ag@methacrylamide CS/poly(ethylene glycol) diacrylate (Ag@MP) micropatterns are successfully fabricated by femtosecond laser maskless optical projection lithography (Fs-MOPL) for the first time. The formation mechanism of core-shell nanomaterial is demonstrated by the local surface plasmon resonances and the nucleation and growth theory. Amino and hydroxyl groups greatly affect the number of Ag@MP nanocomposites, which is further verified by replacing MCS with methacrylated bovine serum albumin and hyaluronic acid methacryloyl, respectively. Besides, the performance of the surface-enhanced Raman scattering, cytotoxicity, cell proliferation, and antibacterial was investigated on Ag@MP micropatterns. Therefore, the proposed protocol to prepare hydrogel core-shell micropattern by the home-built Fs-MOPL technique is prospective for potential applications in the biomedical and biotechnological fields, such as biosensors, cell imaging, and antimicrobial.